L'astragalismo antico e i parallelismi in Grecia moderna: il gioco del Vezyris e altri riti ludici (Mantichora. Italian Journal of Performance Studies, 2020)
I devote my attention to Greek ancient plays by astragals, the knuckle-bones of animals used for games, and their parallels in Modern Greek folk-lore. These ludic rituals are known since Homeric epics and they were very well spread during Antiquity and Byzantine times, as archaeological founds confirm. Plays by astragals had peculiar undertones with respect to fate and chance and they were also linked with divinatory systems as randomizing agents. In fact, the vizier play (βεζύρης) is known in Modern times in Greece and in Southern Italy. It is worthy to be analyzed in comparison with astragalism in classical times as well as with contemporary plays.